A comparative analysis on the use of organic and inorganic fertilizers in cocoa production and their impact on the soil: (a case study of selected cocoa farms in Tafo in the East- Akim District in the Eastern Region) - Koranteng, Victoria Asiamah (2016)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the award of the Degree of Master of Science.